Epoxidized natural rubber toughened polyamide 6/organically modified montmorillonite nanocomposites. (March 2014) - Balakrishnan, Harintharavimal; Nematzadeh, Navid; Wahit, Mat Uzir; Hassan, Azman; Imran, Muhammad
The organically modified montmorillonite (OMMT)-filled polyamide 6 (PA6) nanocomposites were toughened with epoxidized natural rubber (ENR). The PA6, ENR (15–30 wt%) and OMMT (4 parts per hundered (phr)) were melt compounded using counterrotating twin-screw extruder followed by the injection molding. X-ray diffraction (XRD) results indicated that the OMMT platelets in PA6/ENR/OMMT nanocomposites were well dispersed. The Fourier transform infrared (FT-IR) spectra showed graft esterification reaction between PA6 and ENR during processing. It was found that the addition of ENR (up to 20% wt) increased the impact strength and elongation at break of the nanocomposites. Scanning electron microscopy (SEM) images revealed well-dispersed ENR particles. Differential scanning calorimetry (DSC) results showed that the presence of ENR and OMMT had negligible effect on the glass transition of PA6 with a slight decrease in crystallization temperature and crystallinity in PA6/ENR/OMMT nanocomposites.